2016
DOI: 10.1542/hpeds.2015-0222
|View full text |Cite
|
Sign up to set email alerts
|

The Creation of a Pediatric Hospital Medicine Dashboard: Performance Assessment for Improvement

Abstract: PHM dashboards have the potential to guide program development, mobilize faculty to improve care, and demonstrate program value to stakeholders. Dashboard implementation at other institutions and data sharing across sites may help to better define and strengthen the field of PHM by creating benchmarks and help improve the quality of pediatric hospital care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 32 publications
(31 reference statements)
0
26
0
Order By: Relevance
“…For example, Fox et al reported a pediatric medicine dashboard used to measure comparable metrics across four different departments. After the researchers shared the data, they saw increased timeliness of discharges, hospital committee participation, and grant funding [ 30 ]. The authors also offered several suggestions for developing outcome feedback tools: Choose common metrics that can easily be tracked Include multiple domains and multiple metrics to create a clear picture of one's activities Confirm common definitions of metrics amongst subjects Set realistic expectations regarding the number of subjects and administrative effort involved in data collection Integrate data collection into the electronic medical record Take a holistic approach to analyzing complete data rather than focusing on individual metrics Have a plan for sharing data with hospitals and administrators [ 30 ] …”
Section: Resultsmentioning
confidence: 99%
“…For example, Fox et al reported a pediatric medicine dashboard used to measure comparable metrics across four different departments. After the researchers shared the data, they saw increased timeliness of discharges, hospital committee participation, and grant funding [ 30 ]. The authors also offered several suggestions for developing outcome feedback tools: Choose common metrics that can easily be tracked Include multiple domains and multiple metrics to create a clear picture of one's activities Confirm common definitions of metrics amongst subjects Set realistic expectations regarding the number of subjects and administrative effort involved in data collection Integrate data collection into the electronic medical record Take a holistic approach to analyzing complete data rather than focusing on individual metrics Have a plan for sharing data with hospitals and administrators [ 30 ] …”
Section: Resultsmentioning
confidence: 99%
“…Concurrently, several academic groups have described more complete dashboards or scorecards to assess individual hospitalist performance, primarily designed to facilitate comparison across hospitalist groups or to incentivize overall group performance. [8][9][10] However, these efforts are not guided by an overarching framework and are structured after traditional academic models with components related to teaching and scholarship, which may not translate to nonacademic environments. Finally, the Core Competencies for Hospital Medicine outlines some goals for hospitalist performance but does not speak to specific measurement approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Another set of authors described dashboards or scorecards that captured a number of group-level metrics of processes of care that span STEEEP domains and may be applicable to individuals, including Fox et al for pediatrics 8 and Hwa et al for an adult academic hospitalist group. 9 Methods of assessment varied widely across studies and included observations in the clinical environment, 28,30,31 performance in simulations, 32 and surveys about performance. [22][23][24][25][26] A handful of approaches were more automated and made use of informatics 8,9,22 or data collected for other health system purposes.…”
Section: Timelymentioning
confidence: 99%
See 2 more Smart Citations